Engaging consumers in the Australian emergency mental health context: a qualitative perspective from clinicians working in the community. (4th December 2014) - Procter, Nicholas; Backhouse, Julia; Cother, Ingrid; Ferguson, Monika; Fielder, Andrea; Jackson, Adrian; Murison, Julie; Reilly, Julie‐Anne
Abstract Successfully engaging with consumers is seen as an essential component of mental healthcare, yet doing so can be challenging and little is understood about the unique engagement skills and attributes employed by mental health clinicians working in the emergency community context. Consequently, this qualitative study explored the engagement experiences of clinicians to identify the attributes used when engaging with consumers in this unique setting. We conducted two semi‐structured focus groups in July and August 2011 with 16 clinicians employed at one metropolitan mental health organisation in South Australia. Using thematic analysis, we identified two key themes pertaining to the skills and attributes used for successful consumer engagement: (i) building trust, through communication style, an honest approach, facilitating choice and locating trust networks; and (ii) portraying genuine care, through showing respect, offering practical assistance and taking the least restrictive pathway. These findings highlight the unique nature of engagement in the emergency community mental health setting, as well as the flexibility and resourcefulness required to facilitate it.